2022
DOI: 10.1002/ajmg.a.62657
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of expanded noninvasive prenatal testing for fetal chromosome abnormalities in a cohort of 39,580 pregnancies

Abstract: The aim of this study was to determine the predictive value of expanded noninvasive prenatal testing (NIPT‐plus) for fetal chromosome abnormalities in the second trimester (12–26 weeks). We conducted a retrospective cohort study of 39,580 pregnancies with NIPT‐plus. Screening positive cases were diagnosed with karyotyping and single‐nucleotide polymorphism array analysis (SNP array)/copy number variation sequencing (CNV‐seq) with follow‐up. The positive predictive values (PPVs) of trisomy 21, 18, and 13 (T21, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…In present study, a cohort of 23,116 singleton pregnancies from a single center were enrolled to investigate the performance of NIPT-Plus. Our study showed that NIPT-Plus had a comparable PPV for T21 (86.21%) and T18 (55.88%) but a relatively low PPV for T13 (23.08%) compared to previous studies (Chen et al, 2022). The low PPV for T13 may be related to the small number of T13 positive cases in this study, which would increase the fluctuation of PPV.…”
Section: Discussioncontrasting
confidence: 49%
“…In present study, a cohort of 23,116 singleton pregnancies from a single center were enrolled to investigate the performance of NIPT-Plus. Our study showed that NIPT-Plus had a comparable PPV for T21 (86.21%) and T18 (55.88%) but a relatively low PPV for T13 (23.08%) compared to previous studies (Chen et al, 2022). The low PPV for T13 may be related to the small number of T13 positive cases in this study, which would increase the fluctuation of PPV.…”
Section: Discussioncontrasting
confidence: 49%
“…In total, 7845 search results were identified, of which 1862 were duplicates. After screening the remaining 5983 results, 63 articles satisfied the inclusion criteria 12,14–16,18,26–83 . The study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Authors were contacted for seven articles with incomplete data; data were obtained for one 38 and six were excluded. [84][85][86][87][88][89] Included studies were published between 2015 and 2022. Across all included studies, 1 591 459 women underwent cfDNA screening for CNVs, with 5481 receiving a high-risk result (screen-positive rate of 0.34%).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…13,14 In a more recent series of Chen et al including almost 40,000 samples, the PPV in screening microdeletions and duplications was 42%. 15 As most of the studies were done in screening populations, it is unclear why the PPVs are so heterogenous. However, in screening for trisomies, the fetal fraction (FF) is considered as a quality parameter with a strong impact on the test performance and as such also on the PPV.…”
Section: Bevilacqua Et Al Examined the Test Performance In A Prospect...mentioning
confidence: 99%
“…In a more recent series of Chen et al. including almost 40,000 samples, the PPV in screening microdeletions and duplications was 42% 15 . As most of the studies were done in screening populations, it is unclear why the PPVs are so heterogenous.…”
Section: Introductionmentioning
confidence: 99%